A Modified Family of Power Transformations - YANG, Zhenlin (Institutional Knowledge at Singapore Management University, 2006)
A modified family of power transformation, called the dual power transformation, is proposed. The new transformation is shown to possess properties similar to those of the well-known Box-Cox power transformation, but overcomes the long-standing truncation problem of the latter. It generates a rich family of distributions that is seen to be very useful in modeling and analysis of durations and event-times.